Accounting Education Approach in the Context of New Turkish Commercial Code and Turkish Accounting Standards - Cevdet Kızıl; Ayşe Tansel Çetin; Ahmed Bulunmaz (Emerging Markets Journal, 2014)
The aim of this article is to investigate the impact of new Turkish commercial code and Turkish accounting standards on accounting education. This study takes advantage of the survey method for gathering information and running the research analysis. For this purpose, questionnaire forms are distributed to university students personally and via the internet. This paper includes significant research questions such as “Are accounting academicians informed and knowledgeable on new Turkish commercial code and Turkish accounting standards?”, “Do accounting academicians integrate new Turkish commercial code and Turkish accounting standards to their lectures?”, “How does modern accounting education methodology and technology coincides with the teaching of new Turkish commercial code and Turkish accounting standards?”, “Do universities offer mandatory and elective courses which cover the new Turkish commercial code and Turkish accounting standards?” and “If such courses are offered, what are their names, percentage in the curriculum and degree of coverage?” Research contributes to the literature in several ways. Firstly, new Turkish commercial code and Turkish accounting standards are current significant topics for the accounting profession. Furthermore, the accounting education provides a basis for the implementations in public and private sector. Besides, one of the intentions of new Turkish commercial code and Turkish accounting standards is to foster transparency. That is definitely a critical concept also in terms of mergers, acquisitions and investments. Stakeholders of today’s business world such as investors, shareholders, entrepreneurs, auditors and government are in need of more standardized global accounting principles Thus, revision and redesigning of accounting educations plays an important role. Emphasized points also clearly prove the necessity and functionality of this research.